PROBLEM ASPECTS OF ACHIEVEMENT OF CRIMINAL PUNISHMENT GOALS - Urbisinova, Нургуль Еркиновна; Kaliakperova, Елена Николаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The authors of the article consider the key problematic aspects affecting the achievement of the goals of criminal punishment in the Republic of Kazakhstan. The main attention is paid to the issues of the effectiveness of punishment, the problems of the resocialization of convicts and the functioning of the penitentiary system. Nowadays, we are witnessing a constant increase in the crime rate, both in the world as a whole and in Kazakhstan in particular. The criminal community is becoming more organized and professional, their fields of activity are expanding, and more and more people are becoming part of the criminal environment. This trend is accompanied by the low efficiency of judicial institutions for the protection of citizens' rights and the destruction of the crime prevention system, which forces the population to conclude that it is necessary to strengthen repressive measures to counter crime. However, despite the importance of punishment in the prevention of criminal offenses, there are two main strategies in the criminal policy of Kazakhstan: tougher responsibility for serious crimes on the one hand and the use of more humane non-custodial penalties for less serious offenses on the other hand. The authors propose specific mechanisms for improving the goals of criminal punishment and designing a system of types of punishments. When determining punishment, the court should be guided by the norms of the Criminal Code, which define the system and types of punishments, as well as the principles and basic rules for its appointment. The article analyzes the current system of punishments, identifies its shortcomings, and suggests ways to eliminate them. As part of this analysis, it is proposed to amend and supplement a number of norms of the Criminal Code.